Case report: safety and efficacy of lidocaine infusion for the treatment of intractable zoster-associated neuralgia in solid organ transplant recipients - Huan Zheng; Bixin Zheng (Frontiers Media S.A., 2024)
IntroductionSolid organ transplant recipients are at high risk for developing severe zoster-associated neuralgia, and the pharmaceutic therapies of pain management for these patients with limited organ function are challenging. Intravenous lidocaine infusion showed positive analgesic effects and is used for the management of neuropathic pain. This case series reports the safety and effectiveness of intravenous lidocaine infusion in the treatment of intractable zoster-associated neuralgia in solid organ transplant recipients.Case series presentationFive solid organ transplant recipients suffering from refractory zoster-associated neuralgia (numeric rating scale 8-10, despite using high doses of antiepileptic drugs or combined with opioids) were enrolled. Intravenous lidocaine (5 mg/kg ideal bodyweight) was administered over 1.5 h with the monitoring of vital signs. Pain intensity, patient satisfaction, adverse events, typical liver, and kidney function were evaluated. All subjects reported high satisfaction with their treatment and effective pain relief at the 6-month follow-up. One patient experienced short and mild numbness in the mouth and dizziness after the therapy, but no major adverse reactions were reported.ConclusionThis case series provides evidence that intravenous lidocaine infusion provided effective pain relief as an analgesic treatment option for transplant patients with intractable zoster-associated neuralgia.